Myeloid Clonal Infiltrate Identified With Next-Generation Sequencing in Skin Lesions Associated With Myelodysplastic Syndromes and Chronic Myelomonocytic Leukemia: A Case Series - Martin de Frémont, Grégoire; Hirsch, Pierre; Gimenez de Mestral, Santiago; Moguelet, Philippe; Ditchi, Yoan; Emile, Jean-François; Senet, Patricia; Georgin-Lavialle, Sophie; Hanslik, Thomas; Maurier, François; Adedjouma, Amir; Abisror, Noémie; et al. (Frontiers in Immunology, 2021)
Background: Myelodysplastic syndromes (MDS) and chronic myelomonocytic leukemia (CMML) are associated with cutaneous manifestations. Next generation sequencing (NGS) appears as a tool capable of identifying clonal myeloid cells in the skin infiltrate and thus better characterize the link between hematological diseases and skin lesions. Objective: To assess whether skin lesions of MDS/CMML are clonally related to blood or bone marrow cells using NGS Methods: Comparisons of blood or bone marrow and skin samples NGS findings from patients presenting with MDS/CMML and skin lesions in three French hospitals. Results: Among the 14 patients recruited, 12 patients (86%) had mutations in the skin lesions biopsied, 12 patients (86%) had a globally similar mutational profile between blood/bone marrow and skin and 10 patients (71%) had mutations with a high variant allele frequency (>10%) found in the myeloid skin infiltrate. Mutations in TET2 and DNMT3A, both in 4 patients, were the most frequent. Two patients harbored a UBA1 mutation on hematopoietic samples. Limitations: Limited number of patients and retrospective collection of the data. Blood and skin sampling were not performed at the exact same time point for 2 patients. Conclusion: Skin lesions in the setting of MDS/CMML are characterized by a clonal myeloid infiltrate in most cases.